The Effects of Different Fertilization Practices in Combination with the Use of PGPR on the Sugar and Amino Acid Content of Asparagus officinalis - Nikolaos Xekarfotakis (MDPI AG, 2021)
The present study examined the effects of different nitrogen (NH4NO3) and potassium (KNO3) fertilization levels in combination with a nitrogen-fixing, plant growth-promoting rhizobacteria (PGPR) inoculation on the carbohydrate (CHO), amino acid content, and nutrient concentrations (N, P, K) in the spears and the root system of asparagus plants. No significant differences were indicated between the different fertilization treatments regarding N, P, and K in the leaves and roots of asparagus. The inoculation of the asparagus fields with PGPR, no matter the type of the inorganic fertilizer, resulted in increased CHO and amino acid content of the foliage and roots of asparagus. The highest CHO content and amino acid content were recorded in the treatment that combined PGPR inoculation along with KNO3 fertilizer, indicating that higher K applications acted synergistically with the added PGPR.